2021
DOI: 10.1111/ijlh.13607
|View full text |Cite
|
Sign up to set email alerts
|

How I investigate dysgranulopoiesis

Abstract: Dysgranulopoiesis is a condition in which granulocytic production is defective and is most often described in neoplastic conditions. However, it can also be frequently seen in non‐neoplastic conditions. Early suspicion and detection of these non‐neoplastic causes may prevent further invasive and expensive interventions. In this review, we take a look at the various causes of dysgranulopoiesis with an emphasis on non‐neoplastic etiologies, followed by a detailed outline of the laboratory approach for determinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…The most common method for routine diagnosis of hematological pathologies is complete blood count (CBC), which measures cell volume based on a combination of electrical impedance and scatter analysis, as well as non-specific fluorescence labels to provide automated, low-cost, fast, and fairly reliable estimated five-part differential counting of WBCs: neutrophils, monocytes, eosinophils, basophils, and lymphocytes. However, for the more detailed morphological analyses of WBCs needed to diagnose MDS, a blood smear is needed, as this test can detect morphological abnormalities such as nuclear hyper-segmentation and cytoplasmic hypo-granularity [ 7 ]. In a blood smear, typically, manual analysis is performed under a light microscope, which is a labor-intensive method requiring skilled technicians and can take a long time [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common method for routine diagnosis of hematological pathologies is complete blood count (CBC), which measures cell volume based on a combination of electrical impedance and scatter analysis, as well as non-specific fluorescence labels to provide automated, low-cost, fast, and fairly reliable estimated five-part differential counting of WBCs: neutrophils, monocytes, eosinophils, basophils, and lymphocytes. However, for the more detailed morphological analyses of WBCs needed to diagnose MDS, a blood smear is needed, as this test can detect morphological abnormalities such as nuclear hyper-segmentation and cytoplasmic hypo-granularity [ 7 ]. In a blood smear, typically, manual analysis is performed under a light microscope, which is a labor-intensive method requiring skilled technicians and can take a long time [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, infections are a major cause of illness and death in MDS patients [ 5 ], both in patients with neutrophil dysfunction and in patients with neutropenia [ 6 ]. Morphological and physiological abnormalities are common in neutrophils of MDS patients, including nuclear hyper-segmentation, cytoplasmic hypo-granularity [ 7 ], and a reduction in reactive oxygen species (ROS), which are essential for the management of pathogens [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common method for routine diagnosis of hematological pathologies is complete blood count (CBC), which measures cell volume based on a combination of electrical impedance and scatter analysis, as well as non-specific fluorescence labels to provide automated, low-cost, fast, and fairly reliable estimated five-part differential counting of WBCs: neutrophils, monocytes, eosinophils, basophils, and lymphocytes. However, for the more detailed morphological analyses of WBCs needed to diagnose MDS, a blood smear is needed, as this test can detect morphological abnormalities such as nuclear hypersegmentation and cytoplasmic hypo-granularity [7]. In a blood smear, typically, manual analysis is performed under a light microscope, which is a labor-intensive method requiring skilled technicians and can take a long time [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, dysgranulopoiesis is not unique to MDS. Once dysgranulopoiesis is identified according to the abnormal NeuX and NeuZ value as well as microscope observation, correlation with CBC, underlying medical conditions, biochemical and other ancillary investigations is necessary to rule out non‐neoplastic causes 8 . Therefore, NeuX and NeuZ can be used to predict neutrophil dysplasia, but do not directly point to a diagnosis of MDS.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Recent studies have found that CPD parameters generated by automatic hematology analyzer, reflecting leukocyte cellular characteristics like cell complexity or granularity, are possible to use to detect dysgranulopoiesis. 8 Since then, researchers have carried out a large number of studies using different brands of automatic hematology analyzer, all suggesting that there are differences in hematological parameters of peripheral blood samples of healthy people and MDS patients. [9][10][11][12][13] Various studies have found that neutrophil parameter NeuX provided by the automatic hematology analyzer was correlated with the morphological change of neutrophil decreased granules or agranularity.…”
Section: Discussionmentioning
confidence: 99%